Desafios às políticas públicas: análise das relações entre desigualdades socioespaciais e a mobilidade urbana em São Paulo - Reis, Eduardo Castellani Gomes dos (2022)
The present study proposes a reflection on the role of urban mobility and its public policies as protagonists of urban development in São Paulo, through the analysis of its history, development, structures and components. Its importance is justified when we observe that urban mobility has been increasingly studied and thought of as a solution to the urban crisis, not conditioned to its supporting role during the twentieth century. In this way, the research in question starts from the following question: how did urban mobility go from being an adjunct to urban development to one of the great protagonists of the struggle for the improvement of the population's life? We hypothesized that mobility acquires a significant role in history as urban development is no longer tied to land use and land management laws and has as its ultimate objective the improvement of the living conditions of its inhabitants, especially in the reduction of vulnerabilities and inequalities. Thus, the main objectives of this study are: to understand the role of urban mobility in the history of urban development in São Paulo, to analyze the vulnerabilities and inequalities that were structured in the city and, finally, to propose mobility policies and solutions that help in the change. of the living conditions of the population inserted in these vulnerabilities. Organized in three chapters, the dissertation first presents a brief overview of the segregationist urban development of São Paulo and its relationship with urban mobility, based on the investigation of other researchers and theorists, such as Raquel Rolnik, Lúcio Kowarick and Eduardo Vasconcellos. Then, analyzes related to the concepts of vulnerability and inequality centered on three axes: class, gender and race based on studies by institutions such as Ipea (Acronym for Institute of Applied Economic Research in Portuguese), World Bank, ITDP and others; and, finally, the third chapter, which talks about the role of mobility in the fight against socio-spatial inequalities, with the analysis of some axes of action with this objective